2020
DOI: 10.1530/joe-19-0376
|View full text |Cite
|
Sign up to set email alerts
|

Allopregnanolone reduces neuroendocrine response to acute stressful stimuli in sheep

Abstract: The verified hypothesis assumed that centrally administered neurosteroid, allopregnanolone (AL), could affect basal and/or stress-induced activity of the hypothalamic-pituitary-adrenal (HPA) axis in sheep. Four groups (n = 6 each) of luteal-phase sheep were intracerebroventricularly infused for 3 days with a vehicle without stress (control); a vehicle treated with stressful stimuli (isolation and partial movement restriction) on the third day; AL (4 × 15 µg/60 µL/30 min, at 30-min intervals) treated with stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Studies on adult rats have shown that in response to stress, the bed nucleus of the stria terminalis sends an axonal projection into neuroendocrine cell regions of the paraventricular nucleus (PVN) [ 33 ] and relays hippocampal cholinergic signals activating the HPA axis [ 34 ]. The results described in our earlier work [ 25 ] showed that the acute stressful stimuli used, i.e., isolation in combination with partial movement restriction, induced strong neuroendocrine stress response in experimental sheep. This was reflected by an increase in the concentration of corticotropin-releasing hormone (CRH) in the cerebrospinal fluid (CSF), as well as the concentration of adrenocorticotropic hormone (ACTH) and cortisol in the blood.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Studies on adult rats have shown that in response to stress, the bed nucleus of the stria terminalis sends an axonal projection into neuroendocrine cell regions of the paraventricular nucleus (PVN) [ 33 ] and relays hippocampal cholinergic signals activating the HPA axis [ 34 ]. The results described in our earlier work [ 25 ] showed that the acute stressful stimuli used, i.e., isolation in combination with partial movement restriction, induced strong neuroendocrine stress response in experimental sheep. This was reflected by an increase in the concentration of corticotropin-releasing hormone (CRH) in the cerebrospinal fluid (CSF), as well as the concentration of adrenocorticotropic hormone (ACTH) and cortisol in the blood.…”
Section: Discussionmentioning
confidence: 98%
“…This was reflected by an increase in the concentration of corticotropin-releasing hormone (CRH) in the cerebrospinal fluid (CSF), as well as the concentration of adrenocorticotropic hormone (ACTH) and cortisol in the blood. In addition, increased abundance of the CRH and arginine vasopressin mRNA in the PVN was observed [ 25 ]. Considering more broadly the consequences of such types of stress at the molecular level, the results of this study showed the strong stimulation of DNA defense mechanisms in all tissues examined.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations